HUBUNGAN PERILAKU ADIKSI MEDIA SOSIAL (TIKTOK) TERHADAP HASIL BELAJAR AKIDAH AKHLAK SISWA KELAS X MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA TAHUN PELAJARAN 2025/2026 - Nafiisa Saniya Salsabila; Mujiburrohaman Mujiburrohaman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the relationship between TikTok social media addiction behavior and learning outcomes in Akidah Akhlak (Islamic theology and morality) among Grade X students at MA Al-Islam Jamsaren, Surakarta, in the 2025/2026 academic year. The research is motivated by widespread TikTok use among adolescents, which is suspected to distract from learning, especially in subjects aiming to instill religious values. A quantitative correlational design was employed with a total sampling of 66 students (the entire Grade X). TikTok addictive behavior was measured via a closed-ended questionnaire (30 items, 4-point scale), while Akidah Akhlak learning outcomes were taken from mid-semester test scores. Pearson’s correlation test was used for analysis. The results show that students’ TikTok addiction levels were moderate to high (mean score 91.09 on a 30–120 scale; 73% of students in moderate or high category), whereas their Akidah Akhlak outcomes were generally moderate tending to low (mean = 81.58 on a 0–100 scale; 68% in moderate or low category). Normality and homogeneity tests indicated the data met assumptions (p>0.05). The Pearson correlation coefficient was r = 0.144 with p = 0.247, indicating no significant relationship between TikTok addictive behavior and Akidah Akhlak learning outcomes.